Swimming Resistance Band (Strech Cord) Training: An Experimental Study on Swimming Optimisation of Cenderawasih Swimming Club Jayapura Athletes (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Freestyle swimming is one of the numbers in swimming that is often contested. Therefore, training methods must be appropriate in an effort to increase the speed of athletes. This study aims to increase the swimming speed of 50 meters freestyle athletes Cenderawasih Swimming Club Jayapura, Papua through resistance band training using strech cord. Type of experimental research to determine the effect of training on 50m freestyle swimming speed. The population amounted to 144 athletes and the sample used amounted to 20 athletes selected using purposive sampling with the criteria of athletes who have participated in provincial level competitions. Data collection techniques using the 50 meter freestyle swimming test. Hypothesis testing using paired samples t test to determine pretest and posttest differences from resistant band (strech cord) interventions. The results obtained a P-value of 0.001 <0.05 which indicates a significant effect of the resistance band (strech cord) training method on the 50 meter swimming speed of Jayapura Swimming Club athletes. Based on the results of the study, it is concluded that the application of resistance band training needs to be added to the swimming training program in an effort to optimize freestyle swimming speed